2018
DOI: 10.3389/fnins.2018.00824
|View full text |Cite
|
Sign up to set email alerts
|

The Hazard Perception for the Surrounding Shape of Warning Signs: Evidence From an Event-Related Potentials Study

Abstract: Surrounding shape is a very important component of warning signs. Unlike colors, signal words, and pictorials that can directly convey the surface meaning, the surrounding shapes of warning signs convey warning information somewhat obscurely. Most of the researchers who studied this topic investigated the individuals' hazard perception of the surrounding shapes of warning signs by using questionnaires. In addition, the scholars' points about the role of the surrounding shapes are inconsistent. This study, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…Subjects were required to count the number of target stimulus (chairs) in each block in their minds and to report the number upon completion of the block. By this mean, subjects were prompted to focus their attention on the target stimuli, rendering the processing of warning signs task-irrelevant (Ma et al, 2018;Bian et al, 2020;Zhu et al, 2020). Data from a subject would be excluded from final analysis if he (or she) got the numbers wrong in more than one block.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subjects were required to count the number of target stimulus (chairs) in each block in their minds and to report the number upon completion of the block. By this mean, subjects were prompted to focus their attention on the target stimuli, rendering the processing of warning signs task-irrelevant (Ma et al, 2018;Bian et al, 2020;Zhu et al, 2020). Data from a subject would be excluded from final analysis if he (or she) got the numbers wrong in more than one block.…”
Section: Methodsmentioning
confidence: 99%
“…As a type of safety sign, warning sign is a prominent tool used to remind people of potential hazards and instruct them to behave safely. A lot of effort has been devoted to the design and effectiveness of warning signs in the past decades (Chan and Ng, 2010;Ma et al, 2010Ma et al, , 2018Chan and Ng, 2012;Bian et al, 2020;Zhu et al, 2020). In this research trend, the color of warning signs has also received considerable attention because color is essential when the textual message is restricted (Chapanis, 1994;Braun et al, 1995;Borade et al, 2008;Siu et al, 2017;Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exploring the impact of shapes on the perception of warning signs, Ma et al [37] found that people have a stronger negative interpretation from the upright triangle than from the circle.…”
Section: Signal Symbolsmentioning
confidence: 99%